2017
DOI: 10.1111/jnc.14044
|View full text |Cite
|
Sign up to set email alerts
|

Simulations of membrane‐bound diglycosylated human prion protein reveal potential protective mechanisms against misfolding

Abstract: Prion diseases are associated with the misfolding of the prion protein (PrP) from its normal cellular form (PrPC) to its infectious scrapie form (PrPSc). Posttranslational modifications of PrP in vivo can play an important role in modulating the process of misfolding. To gain more insight into the effects of posttranslational modifications on PrP structure and dynamics and to test the hypothesis that such modifications can interact with the protein, we have performed molecular dynamics simulations of diglycosy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…In contrast, when simulated at the surface of the membrane for ∼40−80 ns, PrPC remained stable because it tilted toward the membrane surface, rendering the putative sites for misfolding and oligomerization inaccessible. 598 Misfolding of Huntingtin protein is related to Huntington's disease through pathways that likely involve interactions with the membrane. The poly glutamine region of Huntingtin protein, with a variety of different flanking sequences, was found to induce a variety of membrane effects.…”
Section: Disease-causing Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, when simulated at the surface of the membrane for ∼40−80 ns, PrPC remained stable because it tilted toward the membrane surface, rendering the putative sites for misfolding and oligomerization inaccessible. 598 Misfolding of Huntingtin protein is related to Huntington's disease through pathways that likely involve interactions with the membrane. The poly glutamine region of Huntingtin protein, with a variety of different flanking sequences, was found to induce a variety of membrane effects.…”
Section: Disease-causing Proteinsmentioning
confidence: 99%
“…When simulated in solution, PrPC showed a tendency to misfold during AA simulations of 10–50 ns. In contrast, when simulated at the surface of the membrane for ∼40–80 ns, PrPC remained stable because it tilted toward the membrane surface, rendering the putative sites for misfolding and oligomerization inaccessible . Misfolding of Huntingtin protein is related to Huntington’s disease through pathways that likely involve interactions with the membrane.…”
Section: Lipid Dependence Of Peripheral Membrane Proteinsmentioning
confidence: 99%
“…Inlay shows a model of the conceivable Aβ (red) sequestrating and plaque-promoting action of sPrP (green). Respective non-coloured single channels are shown on the left (g′, g″, g‴) ◂ diglycosylated PrP was a rather poor substrate for the templated misfolding (Camacho et al 2019;Cheng et al 2017;DeMarco and Daggett 2009;Kang et al 2020;Priola and Lawson 2001;Xiao et al 2013). This may well translate into sPrP's blocking activity against the amplification of certain prion strains.…”
Section: Prion Diseasesmentioning
confidence: 99%
“…In this study, we examined the first glycosylation motif, which determines the location of PrP in the cell. Many previous in-vitro and in-silico studies have shown the importance of PrP location in misfolding and aggregation 40,68,69 . The known mechanism for this is that the oligomerization sites are buried in the membrane surface, which prevents the oligomerization and propagation 69 of PrP SC .…”
Section: Discussionmentioning
confidence: 99%
“…Many previous in-vitro and in-silico studies have shown the importance of PrP location in misfolding and aggregation 40,68,69 . The known mechanism for this is that the oligomerization sites are buried in the membrane surface, which prevents the oligomerization and propagation 69 of PrP SC . The T183A mutant not only breaks the first glycosylation motif but also destabilizes the PrP T183A structure.…”
Section: Discussionmentioning
confidence: 99%